Mutagenicity of Flavonoids Assayed by Bacterial Reverse Mutation (Ames) Test - Resende, Flavia Aparecida [UNESP]; Vilegas, Wagner [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Varanda, Eliana Aparecida [UNESP] (Mdpi Ag, 2012)
The mutagenicity of ten flavonoids was assayed by the Ames test, in Salmonella typhimurium strains TA98, TA100 and TA102, with the aim of establishing hydroxylation pattern-mutagenicity relationship profiles. The compounds assessed were: quercetin, kaempferol, luteolin, fisetin, chrysin, galangin, flavone, 3-hydroxyflavone, 5-hydroxyflavone and 7-hydroxyflavone. In the Ames assay, quercetin acted directly and its mutagenicity increased with metabolic activation. In the presence of S9 mix, kaempferol and galangin were mutagenic in the TA98 strain and kaempferol showed signs of mutagenicity in the other strains. The absence of hydroxyl groups, as in flavone, only signs of mutagenicity were shown in strain TA102, after metabolization and, among monohydroxylated flavones (3-hydroxyflavone, 5-hydroxyflavone and 7-hydroxyflavone), the presence of hydroxyl groups only resulted in minor changes. Luteolin and fisetin also showed signs of mutagenicity in strain TA102. Finally, chrysin, which has only two hydroxy groups, at the 5-OH and 7-OH positions, also did not induce mutagenic activity in any of the bacterial strains used, under either activation condition. All the flavonoids were tested at concentrations varying from 2.6 to 30.7 nmol/plate for galangin and 12.1 to 225.0 nmol/plate for other flavonoids. In light of the above, it is necessary to clarify the conditions and the mechanisms that mediate the biological effects of flavonoids before treating them as therapeutical agents, since some compounds can be biotransformed into more genotoxic products; as is the case for galangin, kaempferol and quercetin.
Keywords: mutagenicity; Ames test; flavonoids